1985
DOI: 10.1063/1.336187
|View full text |Cite
|
Sign up to set email alerts
|

The role of activation energy distributions in diffusion related annealing in SiO2

Abstract: Models for annealing processes in damaged, amorphous SiO2 are discussed. Using a series expansion approach, theories developed for diffusion-limited recombination are adapted to allow for a Gaussian distribution of activation energies. It is found that the effect of a distribution having deviation ΔE, and center EA can be accounted for by using an effective diffusion coefficient, D̃, such that in the series expansion any power (n) is defined by (D̃)n=Dn0 exp  1/2  (nΔE/kT)2 exp(−nEA/kT). This form is more comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Upon integration over all energies, an effective diffusion coefficient is obtained Deff=D00.25emexp()U0/Texp0.25em()UW2/4T2. Similar approaches have been used in the studies of hydrogen diffusion in silica glass (Devine, ; Shelby & Keeton, ). Using equation , Farrell et al () define an analytical expression of the implanted density as a function of solar zenith angle assuming dynamic equilibrium on timescales much less than a lunation: italicnvnSWvSWcos()Z where v=D0h1exp()U0/Texp0.25em()()UW2/4T2 is defined as the diffusive velocity, or in terms of a diffusive lifetime τ2=h/v=D1h2exp()U0/T0.25emexp0.25em()()UW2/4T2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon integration over all energies, an effective diffusion coefficient is obtained Deff=D00.25emexp()U0/Texp0.25em()UW2/4T2. Similar approaches have been used in the studies of hydrogen diffusion in silica glass (Devine, ; Shelby & Keeton, ). Using equation , Farrell et al () define an analytical expression of the implanted density as a function of solar zenith angle assuming dynamic equilibrium on timescales much less than a lunation: italicnvnSWvSWcos()Z where v=D0h1exp()U0/Texp0.25em()()UW2/4T2 is defined as the diffusive velocity, or in terms of a diffusive lifetime τ2=h/v=D1h2exp()U0/T0.25emexp0.25em()()UW2/4T2.…”
Section: Methodsmentioning
confidence: 99%
“…Similar approaches have been used in the studies of hydrogen diffusion in silica glass (Devine, 1985;Shelby & Keeton, 1974). Using equation (6), Farrell et al (2017) define an analytical expression of the implanted density as a function of solar zenith angle assuming dynamic equilibrium on timescales much less than a lunation:…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the excess oxygen reactive species in the plasma, Ar þ and O þ ion bombardment to the growing film could be another factor causing the formation of the O-rich film, because high-degree O-rich films did not form at V b ¼ 0 V, but they did form at V b ¼ À100 V, as indicated in Fig. 1, and it has been found that O-rich related defects could be generated in silica by Ar þ implantation [5,6]. Optical absorption of the SiO x films deposited on bare silica plates was measured before and after thermal annealing at temperature of 400 C for 30 min.…”
Section: Fig 1 Dependences Of O=si Atomic Ratio Of Sio X Films On Apmentioning
confidence: 99%
“…These phenomena can be associated with the defects in the films. The defects in silica have been well-studied using electron-spin resonance technique [5,6]. It was found that there are three principal non-impurity-related defects in amorphous SiO 2 : paramagnetic oxygen vacancy centre (E 0 ) and its variants, non-bridging oxygen (NBO) hole centre and peroxy radical with trapped hole.…”
Section: Fig 1 Dependences Of O=si Atomic Ratio Of Sio X Films On Apmentioning
confidence: 99%
See 1 more Smart Citation